The Dethronement of Bernardo II in 1615. The Role of a Violence and Christianity in Ideology of Power in Kongo in the first half of the 17th century - PIĘTEK, Robert (Historia i Świat, 2021)
The article presents a spectacular occurrence of violence in Kongo during the first half of the 17th century related to power struggles, shown mainly on the example of Bernardo II being dethroned by Álvaro III. Executing rivals in such a striking fashion was both meant as a warning to potential rebels against taking similar actions, and as a way to emphasize the monarch’s power. Christianity played also important role in Kongolese ideology of royal power, which obviously did not exclude referring to pre-Christian customs. Despite such actions, the Kongolese monarchs did not manage to gain full control of the territory during the first half of the 17th century or to counteract the revolts.